Participatory media new and old: semiotics and affordances of museum media. Issue 4 (7th August 2016) - Noy, Chaim
ABSTRACT: The move from "old" to "new" media centrally involves a shift in participatory possibilities, through which individuals and communities differentially access and populate the public sphere, assume voice, and partake in open discussion and debate. This paper offers a rich ethnographic case study of new participatory media in the shape of commenting systems in museums. By portraying the similarities and the differences in communicative affordances between two museum media—traditional visitor books, on the one hand, and a digital and immersive interface, on the other hand—light is shed on how media invite and intervene in possibilities for public participation. Furthermore, with their emphasis on visual design and display, studying participatory public media in museums helps highlight the semiotic construction of the public sphere as such, and how the notion of the public and laypersons' contributions are materially displayed. Analysis of communicative affordances reveals the politics of remediation, and supports recent hesitations with regard to the promise of newer and "smarter" media: digital media affords more interaction than their analogue predecessors, but participatory content-production via analogue media is found to be discursively richer on a number of grounds.